Efeito do peso ao nascimento e do sexo sobre a ingestão de colostro, desempenho e resposta imune de leitões - Paula, Ygor Henrique de (2022)
The sexual category has the ability to impact several indexes at different stages of the piglets' life, such as performance, consumption and survival, as well as promoting variations in maturation and modulation of gastrointestinal functions and structures. Added to this factor, swine production currently faces an increase in the number of piglets born total in the same litter, which generates high weight variability. In view of this, the hypothesis of this work is that the interaction of sex and birth weight generates variations in the amount of colostrum ingested, performance and immune response of piglets during the maternity and nursery phases. The objective was to evaluate the effect of sex and birth weight on colostrum intake, performance and immune response of piglets in these phases. The study was conducted at the Animalnutri and Auma Tecnologia Swine Experimental Center facilities in Patos de Minas, Minas Gerais, Brazil. During the farrowing phase, 757 piglets from sows with parities 1 until 10 order were used. After weaning at 22 days of age, 228 piglets remained in the study. A completely randomized design in a 2x3 factorial scheme was used, considering two sex categories (female and male) and three birth weight classes (BWC) (low - 0.8 to 1.1 kg; medium - 1.101 to 1.4 kg and high - 1.401 to 1.7 kg). Each piglet was an experimental unit. At birth and after 24 hours, serum glucose concentration was measured. The calculation of colostrum intake was determined based on a specific equation. The piglets were individually weighed at birth, 24 hours after farrowing, at weaning, as well as at 7, 14 and 42 days of nursery phase, where with the values of supply and leftovers of feed, the average daily gain (ADG), average daily feed intake (ADFI) and feed conversion ratio (FCR) were calculated. Blood samples were collected from six animals per treatment on the 4th day after weaning for the analysis of immune response (IL-10 and TNF-α) and plasma concentration of immunoglobulin G (IgG) by ELISA test. During the entire experimental period, notes regarding mortality, removal and number of medicated animals were carried out. All data were analyzed using the statistical package of the SAS software. Serum glucose content was not influenced by treatments (p>0.05). High birth weight piglets ingested a greater amount of colostrum (p<0.001). Male piglets had higher removal rate added to mortality (p=0.027). High weight females had a higher percentage of medication (p<0.001). Piglet body weight was higher for those with high birth weight in all measurements (p<0.001). ADG and ADFI during the nursery phase were influenced by BWC (p<0.001). Low birth weight piglets had a lower concentration of TNF-α (p=0.009). There was no effect on IL-10 concentration (p>0.05). Males tended to have a higher serum IgG concentration (p=0.067). In conclusion, there was no interaction for sex and BWC of piglets for colostrum intake, performance and immune response during farrowing and nursery phases. High birth weight piglets had a higher colostrum intake, while low birth weight piglets had a lower pro-inflammatory response in the first week of nursery phase. The BWC determines the weights at weaning and at leaving nursery phase, as well as the ADG and ADFI profiles throughout the farrowing and nursery phases. Male and low weight piglets had higher removal and mortality rates during the farrowing phase. Males tend to had a higher IgG concentration after weaning.